Factors which Affect the Interest of Accounting Student Interest Toward Use of an Accounting Software - Thaddeus Kevin Hendartha; I Made Pande Dwiana Putra (E-Jurnal Akuntansi, 2024)
This research was made to determine some of the many factors that affect student interest on using accounting software which hypothetically are computer anxiety, computer attitude, and computer self efficacy. The population of this research are the 2019th Accounting Student of Udayana University, therefore this research utilizes questionnaire as an instrument to gather a total number of 74 convenience gathered samples of respondents. This research used the multiple linear regression with the help of 22nd version of SPSS. Result shows that computer self efficacy has positive effect, while contrary computer anxiety has negative effect towards someone’s perceived ease of use of computer. Computer attitudes appearently does not affect the interest of an accounting student on using accounting software, reason is that the questionnaire is unable to specify the usage of computer.